Investigation and characterisation of viral and host factors that impact intraspecies EBOV infectivity using a viral pseudotyping assay - Dey, Jayasree (2023)
Zaire Ebola Virus (EBOV) is the etiological agent of Ebola Virus Disease, which is characterised by inflammation and damage to endothelial cell linings that can rapidly advance to internal haemorrhaging and multi-organ failure, with mortality rates observed as high as 90%. As a zoonotic virus, current evidence suggests that bats may be the natural reservoir for EBOV. With outbreaks becoming more frequent, EBOV remains an ongoing threat to public health. Further work investigating the intraspecies variation present within EBOV and the viral and host genetic factors that impact viral fitness, is needed to provide insight into potential genetic drivers of virus spillover and pathogenesis.